In situ and experimental evidence for effects of elevated pH on protistan and metazoan grazers. (22nd December 2017) - Hansen, Benni W; Andersen, Christian M B; Hansen, Per J; Nielsen, Torkel G; Vismann, Bent; Tiselius, Peter
Abstract: Plankton succession was studied in a hyper-eutrophic stratified estuary, Mariager Fjord, Denmark. Above the pycnocline (15 m) pH increased from 8.5 to 9.2 and the oxygen increased to super saturation after 5 d of sunny weather due to high primary production. The protistan grazers were dominated by heterotrophic dinoflagellates and mixotrophic and heterotrophic ciliates. Metazooplankton was dominated by meroplankton, rotifers and the copepod, Acartia tonsa, all with a relatively low biomass. Cirriped nauplii occupied the upper strata while polychaete larvae populated the whole water column. Bivalve larvae occurred occasionally above the pycnocline even at very high pH. In pH challenge experiments, the mixotrophic ciliate Mesodinium rubrum was the least pH tolerant species, followed by Strombidium spp., which did not cope well with seawater pH > 8.5. Some heterotrophic dinoflagellates were more tolerant with net growth at pH > 9. The predominant rotifer Synchaeta sp. tolerated up to pH 9.5 and the copepod survived pH 10 but stopped producing eggs at pH 9.5 with unaffected egg hatching success. The polychaete and cirriped larvae tolerated pH 9.5, but bivalve larvae showed decreased survival already at pH 8.5. In situ distribution patterns and pH challenge experiments suggest that pH indeed contribute to structuring zooplankton distribution.